Efficacy of Maggot Therapy on Staphylococcus aureus and Pseudomonas aeruginosa in Diabetic Foot Ulcers: A Randomized Controlled Trial. Issue 1 (January 2019) - Malekian, Azam; Esmaeeli Djavid, Gholamreza; Akbarzadeh, Kamran; Soltandallal, Mehdi; Rassi, Yavar; Rafinejad, Javad; Rahimi Foroushani, Abbas; Farhoud, Amir Reza; Bakhtiary, Ronak; Totonchi, Mehrangiz
Abstract : PURPOSE: This study was conducted to evaluate the antimicrobial effects of medicinal maggots of Lucilia sericata on Staphylococcus aureus and Pseudomonas aeruginosa on diabetic foot ulcers (DFUs). DESIGN: Randomized controlled trial. SUBJECTS AND SETTING: The sample comprised 50 adult patients from the clinic of the Academic Center for Education, Culture and Research of Tehran University of Medical Sciences, Iran. All participants who had at least 1 DFU present for at least 12 weeks, an arterial brachial index value of more than 0.6, and a hemoglobin A1c value of less than 8% were included in this study. METHODS: Subjects were randomly selected for the maggot-treated (treatment) or conventional treatment (control) group. Conventional treatments such as antibiotic therapy, debridement, and offloading were done for both groups, but maggot therapy (MT) was added to the protocol of the treatment group. Bacterial burden was monitored and compared for both groups using cultures collected using swab technique. Wound secretions were measured and compared in both groups. RESULTS: The number of infected cases with S aureus in the treatment group was significantly reduced after 48 hours in comparison with the control group ( P = .047). The number of infected cases with P aeruginosa was significantly reduced after 96 hours ( P = .002). We also found that wound secretions in the treatment group were significantly higher than in the control group ( P < .00). CONCLUSIONS: Our findings indicate that MT is a safe and efficacious treatment of DFUs.